Responsible Mining: Challenges To Make It Right - Government Perspective - M. Z. A., Wahab; Muhammad Hafiz, Mazwir; Nurul Ain, Ismail (Penerbit Universiti Malaysia Pahang, 2017)
The mining industry has impacted positively on the economy of the Nation and the State over the years. It has created employment for the local community, contributed to the state revenue, and is an economic driver especially in the development of remote mineralised areas. The Federal Constitution has laid down the jurisdiction of the Federal and State governments with regards to the development of mineral. Under the 9th Schedule of the Constitution, the Federal government is responsible for the development of mineral resources; mines, mining, mineral and mineral ores; oil and oilfields; purchase, sale, import and export of mineral and mineral ores; petroleum products; regulation of labour and safety in mines and oilfields; whilst for the State, the issuance and licenses for prospecting; mining leases and certificates. The responsibility of rehabilitation of mining land comes under both parties. Through these enabling powers, both the State and Federal governments have promulgated the Mineral Development Act 1994 (MDA) and the various State Mineral Enactments (SME) respectively. Both these laws outline the responsibilities of the tenement holders to their employee, the State, society as well as the environment. Apart from these laws, there are other related laws such as Environment Quality Act (EQA) and Occupational Safety and Health Act (OSHA). The concept of sustainability and concern for the environment has created a new challenge to the industry. Acknowledging the importance of mining is the desire of the government when issuing the tenement that the holder will carry out their exploration, mining and rehabilitation activities responsibly with the spirit of mining for closure